DIFFUSE INTERSTELLAR BANDS (DIBs) AS A TRACER OF GALACTIC WARP - Nur Istiqomah, Ade
Galactic warp is a phenomenon in which the outer Galactic disk warped away towards NGP in the north and SGP in the south. Warp appears in various Galactic disk tracers such as neutral hydrogen, molecular clouds, and stellar clusters. Warp studies based on tracer distributions suggest that the warp started at R 1 kpc from the Sun meanwhile recent stellar kinematic studies propose farther distance at R 4 kpc. Diuse Interstellar Bands (DIBs), a set of absorptions appear in spectra of reddened object, is considered to be a potential Galactic disk tracer for it is not easily saturated. Around 500 DIBs have been identied yet its exact carriers still remain misteries. This thesis aims to trace Galactic warp in the Third Galactic Quadrant (TGQ) from spatial distribution of a DIB with c 661,36 A (DIB 6614). DIB 6614 were extracted from Gaia-ESO Spectroscopic Survey high resolution (R 17000 dan 47000) cool star spectra meanwhile corresponding stellar distance estimation taken from Gaia Data Release 2. Warp in TGQ is inspected in six elds, all located in b < 0 °. Tracing the Galactic warp in aforementioned elds of view show increasing DIB 6614 abundance over stellar distance. However, we can't draw strong conclusion that this behaviour is caused by the Galactic warp as there are no comparison elds located above and in the formal Galactic plane. To be able to conclude that the warp also aects DIB 6614 carrier distribution, additional elds located in b > 0° and b 0°are necessary. Keywords: